HIV destigmatization: perspectives of people living with HIV in the Kumasi Metropolis in Ghana - Armstrong-Mensah, Elizabeth; Ofori, Emmanuel; Alema-Mensah, Ernest; Agyarko-Poku, Thomas (Frontiers in Reproductive Health, 2023)
Background Human immunodeficiency virus (HIV)-related stigma has been identified as one of the principal factors that undermines HIV prevention efforts and the quality of life of people living with HIV (PLWH) in many developing countries including Ghana. While studies have been conducted on HIV-related stigma reduction, very few have sought the views of PLWH on how this might be done. The purpose of the study was to (i) identify factors that cause HIV-related stigma in Ghana from the perspective of PLWH, (ii) identify challenges that HIV-related stigma poses to the treatment and care of PLWH, and (iii) to obtain recommendations from PLWH on what they think various groups (community members, health care providers, and adolescents) including themselves should do to help reduce HIV-related stigma in Ghana. Methods A mixed methods cross-sectional study design was used to collect data from 404 PLWH at the Suntreso Government Hospital in the Kumasi Metropolis of Ghana across six domains using Qualtrics from November 1–30, 2022. Quantitative data was analyzed using the Statistical Package for Social Sciences (SPSS) version 26 and the Statistical Analysis System (SAS) version 9.4. Qualitative data was analyzed using a thematic approach. Results Most of the study participants (70.5%) said HIV-related stigma in Ghana is due to ignorance. Of this population, 90.6% indicated that they had experienced stigma because they have HIV, causing them to feel depressed (2.5%), ashamed (2.2%), and hurt (3.0%). Study participants (92.8%) indicated that the challenges associated with HIV-related stigma has affected their treatment and care-seeking behaviors. Recommendations provided by study participants for HIV destigmatization include the need for PLWH not to disclose their status (cited 94 times), community members to educate themselves about HIV (96.5%), health care providers to identify their stigmatizing behaviors (95.3%), health care providers to avoid discriminating against PLWH (96.0%), and the need for adolescents to be educated on HIV and how it is transmitted (97.0%). Conclusion It is important for the government and HIV prevention agencies in Ghana to target and address co-occurring HIV-related stigma sources at various levels of intersection simultaneously This will help to shift harmful attitudes and behaviors that compromise the health and wellbeing of PLWH effectively.